2003
DOI: 10.1146/annurev.phyto.41.052002.095647
|View full text |Cite
|
Sign up to set email alerts
|

PERSPECTIVES ONPLANT ANDSOILNEMATOLOGY

Abstract: Key Words academic programs, discoveries, ecology-based management, international programs, nematodes as pathogens, professional societies, status of nematology, trophic groups s Abstract During my career in Plant Pathology/Nematology, many major advancements have occurred in the study of nematodes-even with their being largely soilborne and thus often overlooked. These biotrophic organisms include the most widespread and important group of plant pathogens-the root-knot nematodes Meloidogyne species-which atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Recently, interactions among the microorganism, nematode target, plant and environment have been well reviewed and emphasized (Kerry, 2000; Barker, 2003; Davies, 2005; Dong & Zhang, 2006). Sustainable working methodologies have been proposed, including integrated pest management (IPM).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, interactions among the microorganism, nematode target, plant and environment have been well reviewed and emphasized (Kerry, 2000; Barker, 2003; Davies, 2005; Dong & Zhang, 2006). Sustainable working methodologies have been proposed, including integrated pest management (IPM).…”
Section: Resultsmentioning
confidence: 99%
“…They were reared on an artificial diet (a wheat germ‐based basic diet with a vitamin mix) in a climate chamber at 24°C and 70% humidity under a 16/8‐hr day/night light cycle. Root‐knot nematode, M. incognita , is a globally distributed plant parasite that feeds on the roots of numerous host plants, including commercial tobacco Nicotiana tabacum (Barker, ; Koenning et al, ), in addition to being found in the natural habitat of N. attenuata plants (R. Machado, personal communication). Second‐stage juveniles (J2s) of M. incognita (nematode hereafter) were obtained from a biological supply company (Hettema Zaaizaad en Pootgoed Coöperatie [HZPC Holland B.V.], Metslawier, the Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the inactivation specificity of AtGCL compared with those of GCL from T. brucei (20), Ascaris suum (32), and Onchocerca volvulus (33) suggests that the design of anti-nematode compounds is possible. Although these nematodes are human parasites, the generation of inhibitors against nematodes that attack crop and non-crop plants can also be envisioned (40).…”
Section: Expression and Purification Of Atgcl-mentioning
confidence: 99%